Ultrasonography of the salivary glands in the diagnosis of Sjögren’s syndrome secondary to rheumatoid arthritis – a probabilistic approach - Abogabal, Mervat; ElBakry, Samah A.; Aboulfotouh M. Khali, Adham; Hammoda, Rasha Mahmoud; El-Asfahani, Marwa Adel; Morad, Caroline Samy (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. To evaluate the role of salivary gland ultrasound (SGUS) in differentiating rheumatoid arthritis (RA) patients with or without Sjogren’s syndrome (SS) using a probability method and to study the relation between secondary SS (sSS) and RA disease characteristics. Material and methods. One hundred RA patients with disease duration ≥5 years underwent detailed history taking, examination, routine laboratory testing, Schirmer’s test, unstimulated salivary flow rate and SGUS of the 4 major salivary glands using Salaffi and Outcome Measures In Rheumatoid Arthritis Clinical Trials (OMERACT) scores. Results. Patients sum with probabilities for sSS ≤20% and ≥80% were (39/100) before and (90/100) after SGUS with a highly significant difference (p<0.001).There was significantly more frequent carpal tunnel syndrome (CTS), longer RA disease duration and higher anti-cyclic citrullinated peptide antibodies (anti-CCP) in RA patients with sSS compared to those without (p<0.05). There was highly significant agreement between Salaffi and OMERACT scores in gland evaluation by kappa test. The highest ultrasound OMERACT score of SG showed significant positive correlation with both Disease Activity Score-28-Erythrocyte Sedimentation Rate (DAS-28 ESR score) and ESR in RA patients. Conclusion. Secondary SS is frequent in RA patients especially in association with longer disease duration, higher anti-CCP antibody titer and CTS. SGUS is a useful tool that helps diagnosing and grading the severity of SS in RA. SS severity correlates with RA disease activity.